Genetic diversity among genotypes of Parkia platycephala (Benth.), a typical tree of northeastern Brazil - Oliveira, Raiane de Sousa; Costa, Gérson do Nascimento; Silva, Raimundo Nonato Oliveira; Lima, Paulo Sarmanho da Costa; Araújo Neto, Raimundo Bezerra de; Lopes, Ângela Celis de Almeida; Martins, Francielle Alline (Acta Scientiarum. Biological Sciences, 2024)
Parkia platycephala (Fabaceae) is a useful tree. The leaves are rich in protein, fiber and minerals and are good quality, low-cost fodder for animals, making it a great option for animal feed during the dry season in Northeast Brazil. In addition, wood is used in small buildings and as fuel. With the aim of exploring genetic variation within the species, we have assessed the molecular and morpho-agronomic characteristics of 10 accessions (F1 - F10) of the species originating from the same location and maintained in the Forage Collection at Embrapa Meio Norte. Clustering analyses based on the amplicons generated by 12 inter simple sequence repeat (ISSR) primers and on 36 qualitative/quantitative markers separated the accessions into two groups, the constituents of which were dependent on the characteristics considered. The most divergent genotypes according to ISSR analysis were F3 and F8. Morpho-agronomic analysis identified F2 and F7 as the most divergent, while the traits that contributed most (36.5%) to total diversity were, in order of importance, mature inflorescence length, stem length, immature inflorescence width, seed weight and pedicel length. The results revealed that there is sufficient genetic variability among the studied accessions. These accessions with greater diversity are candidates for actions that promote the conservation, domestication and genetic improvement of the species.